Binding of RBP-Jκ (CSL) Protein to the Promoter of the Kaposi’s Sarcoma-Associated Herpesvirus ORF47 (gL) Gene Is a Critical but Not Sufficient Determinant of Trans-activation by ORF50 Protein - Chang, Pey-Jium (2009)
ORF50 protein activates KSHV lytic cycle. The promoter of an early lytic cycle gene ORF47, encoding envelope protein gL, is activated by an interaction between ORF50 protein and RBP-Jκ. In ORF47p only one of two sequences fitting the consensus RBP-Jκ recognition site strongly binds RBP-Jκ and confers a response to ORF50 protein. Flanking sequences 5’ to the RBP-Jκ binding site are required to confer a maximal response to ORF50 protein. Not all mutant ORF50 response elements in the ORF47p that are bound by RBP-Jκ are sufficient to confer maximal ORF50 responsiveness. Four sequences containing an RBP-Jκ site and flanking sequences characteristic of the ORF50 response element in ORF47p were identified in human DNA. All bound RBP-Jκ, but only one responded robustly to ORF50 protein. We propose models for the possible function of ancillary sequences flanking the RBP-Jκ-binding element which are crucial for mediating ORF50 transactivation.